Marked Increase of Activated Factor VII in Uremic Patients - Kario, Kazuomi; Matsuo, Takefumi; Matsuo, Miyako; Koide, Masanobu; Yamada, Tsutomu; Nakamura, Shin; Sakata, Toshiyuki; Kato, Hisao; Miyata, Toshiyuki (Thrombosis and Haemostasis, 1995)
We investigated plasma activated factor VII (FVIIa) levels in uremic patients (nondialysis group: n = 38; dialysis group: n = 36) and healthy controls (n = 32). We also measured the plasma levels of thrombomodulin (an indicator of endothelial cell injury) and tissue factor. Plasma FVIIa showed a marked increase in the nondialysis group (mean [95% confidence interval]: 4.6 [4.1-5.1] ng/ml, p <0.0001) with the progressive impairment of renal function, as indicated by the serum creatinine level, when compared with the 32 controls (2.8 [2.5-3.1] ng/ml), and was further increased in the dialysis group (6.1 [5.5-6.8] ng/ml, p <0.001 vs. nondialysis group). Plasma levels of thrombomodulin and tissue factor were also higher in the nondialysis group than the control group, and were further increased in the dialysis group. Plasma tissue factor levels did not show any correlation with FVIIa or thrombomodulin in both the nondialysis and dialysis groups. Thus, circulating tissue factor appears to be released by a different mechanism from thrombomodulin and may not contribute to the direct activation of factor VII in uremic patients. On the other hand, the plasma level of thrombomodulin was positively correlated with that of FVIIa in the nondialysis group, and this correlation was independent of renal function. Thus, enhanced conversion of factor VII zymogen to FVIIa, probably related to endothelial cell injury, may be a risk factor for cardiovascular events in uremic patients.